Rateless collection tree protocol on TinyOS - Lee, Pei Ying (2016)
Increasing proliferation of wireless technologies had continuously opened up new area of research in the Wireless Sensor Networks (WSNs). This project will focus on the research of the reliability and efficiency packet transmission using Collection Tree Protocol and Luby-Transform Code. Collection Tree Protocol is a highly reliable routing protocol used in the dynamic WSNs for the transmission of data packets. It is able to update the communication link between nodes and repairing of routing loops on the fly to adapt to the current network traffic. Luby-Transform Code reduces the amount of control messages needed in identifying lost packets. In addition, it is able to generate an unlimited number of encoded packets to account for missing packet during transmission. The two programs were integrated to produce a Rateless Collection Tree Protocol. Both can compensate each other in lacking areas to provide a better and reliable collection protocol that can be used in the WSNs. Experiments were conducted to analyze the output of the implemented program. Packet duplication is still an issue in the current program. Modifications can be made in the duplication check as future improvement to reduce packet duplication that occurs in the network. Multi-hop communication in Collection Tree Protocol helps to extend the network coverage as nodes can be easily added to the network. This provides flexibility of the network as the network can be form dynamically.